Pengembangan Aplikasi Sistem Pendukung Keputusan Rekrutmen Perawat Menggunakan Metode Weighted Product - Dedy Armiady (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
Work that requires high accuracy and must be done repeatedly is work that must be completed using a computer. This work will certainly be very difficult to complete if you only rely on human power which has weaknesses in terms of memory and speed. Currently, many agencies and companies are aggressively implementing computerized technology to support good management, one of which is a hospital. In addition to patient data management and other important data, cases of nurse recruitment are also things that need to be considered to be resolved by the computer. This study aims to develop a web-based decision support system using a weighted product model to calculate alternative rankings. The results obtained are that the weighted product method can be used to calculate the ranking of prospective nurses through 12 specified criteria, where from several applicants, 3 prospective nurses with the highest rank are taken. The decision support system application in this study was developed using the PHP and MySQL programming languages with the CodeIgniter framework